Fecal DNA methylation markers for detecting stages of colorectal cancer and its precursors: a systematic review - Raut, Janhavi R.; Guan, Zhong; Schrotz-King, Petra; Brenner, Hermann (Clinical epigenetics, 2020)
DNA methylation biomarkers in stool may have applications in early colorectal cancer (CRC) detection; however, their association with stages of CRC carcinogenesis or their performance in detecting various stages is unclear. We aimed to systematically review the evidence for DNA methylation markers in stool for risk stratification or detection of specific CRC stages, as well as precursors of CRC.